Skewed Sociolinguistic Awareness of a Native Non-standard Dialect: Evidence from the Cypriot Greek Writing of Greek Cypriot Students - Ayiomamitou, Ioli; Yiakoumetti, Androula (Frontiers in Psychology, 2017)
Over the last fifty years, sociolinguistic research in settings in which a regional, social or ethnic nonstandard linguistic variety is used alongside the standard variety of the same language has steadily increased. The educational implications of the concomitant use of such varieties have also received a great deal of research attention. This study deals with variation and its implications for education by focusing on the Greek Cypriot context which is ideal for investigating the linguistic profiles of speakers of proximal varieties as the majority of Greek Cypriots are primarily educated in just one of their varieties: the standard educational variety. The aim of our study was to understand Greek Cypriot primary school pupils’ sociolinguistic awareness via examination of their written production in their home variety (Cypriot Greek dialect). Our assumption was that, because written production is less spontaneous that speech, it better reflects pupils’ conscious awareness. Pupils were advised to produce texts that reflected their everyday language with family and friends (beyond school boundaries). As expected, students’ texts included an abundance of mesolectal features and the following were the ten most frequent: (1) palato-alveolar consonants, (2) future particle [enːá] and conditional [ítan na] + subjunctive, (3) consonant devoicing, (4) CG-specific verb stems, (5) final [n] retention, (6) [én/ éni] instead of [íne], (7) CG-specific verb endings, (8) [én/é] instead of [ðen], (9) elision of intervocalic fricative [ɣ], and (10) CG-specific adverbs. Importantly, in addition to the expected mesolectal features that reflect contemporary Cypriot Greek, students included a significant and unexpected number of basilectal features and instances of hyperdialectism (that are not representative of today’s linguistic reality) which rendered their texts register-inappropriate. This led us to conclude that Greek Cypriot students have a skewed sociolinguistic awareness of variation within their first dialect and a distorted impression of their own everyday language. We argue that the portrayal of Cypriot Greek in its basilectal form was performed intentionally by students to distance themselves from a socially-constructed identity of a rural, uneducated, and stigmatised nonstandard-dialect speaker. The study is of international relevance as it deals with sociolinguistic issues that pertain to all bidialectal speakers.